Taxonomic revision of the subgenus Eutricharaea Thomson in Egypt, with a key to the species and the description of two new species (Hymenoptera, Anthophila, Megachilidae, genus Megachile Latreille) - Praz, Christophe; Al-Shahat, Ahmed M.; Gadallah, Neveen S. (Zootaxa, 2021)
The subgenus Eutricharaea Thomson of the genus Megachile Latreille (Hymenoptera: Megachilidae) in Egypt is revised. Fifteen species are recognized, of which two are new: Megachile laniventris Praz sp. nov. and M. rufomandibularis Praz sp. nov. In addition, three unclear taxa known from few specimens in one sex are documented to facilitate future work. The following new synonymies are proposed: M. microxantha Cockerell 1937, M. privigna Rebmann 1968, and M. submucida Alfken 1926 are synonymized with M. leucostoma Pérez 1907 (syn. nov.); M. blanda Rebmann 1968 with M. walkeri Dalla Torre 1896 (syn. nov.); M. uniformis Alfken 1934 (not M. uniformis Mitchell 1929) and the replacement name M. minutuloides Alfken 1936 with M. minutissima Radoszkowski 1876 (syn. nov.); and M. tkalcui Zanden 1996 with M. rugipuncta Alfken 1934 (syn. nov.). Lectotypes are designated for M. soikai Benoist 1961, M. rugipuncta, M. tenuistriga Alfken 1938, M. niveascopa Ferton 1908, and M. naevia Kohl 1906. The previously unknown males of M. impressipuncta Alfken 1934 and M. rugipuncta, as well as the undescribed female of M. soikai are described. Illustrated keys for both males and females are provided and DNA barcodes are published for most species.